Transit time flow measurement guiding the surgical treatment for anomalous origin of the right coronary artery: A case report - Jiritano, Federica; Leone, Angelo; Greco, Francesco; Leporace, Mario; Bova, Carlo; Aiello, Vincenzo; Serraino, Giuseppe Filiberto; Mastroroberto, Pasquale (Frontiers in Cardiovascular Medicine, 2022)
Anomalous origin of a coronary artery from the opposite sinus of Valsalva (ACAOS) in symptomatic patients is a rare but serious finding whose treatment consists of a surgical correction. The surgical treatment has a level of complexity that could vary from unroofing and ostioplasty to coronary artery bypass grafting. We present our management of a 59-year-old woman presenting with chest pain and dyspnea for right ACAOS with an interarterial route. The right coronary artery (RCA) was bypassed with the right internal thoracic artery. An intraoperative transit time flowmetry (TTFM) showed a competitive flow from the native RCA. RCA proximal ligation site was identified intraoperatively, considering the best mean graft flow and the absence of ischemic events. The patient was discharged after a week without adverse events. The 1-year follow-up was uneventful. The intraoperative use of TTFM could guide the surgeon’s hand making straightforward the surgical treatment for ACAOS.